2019
DOI: 10.1177/1757975918789346
|View full text |Cite
|
Sign up to set email alerts
|

Development of a national conceptual framework and measuring tool for Organisational Social Responsibility and Accountability for Health (OSRAH)

Abstract: Organisations can have a significant impact (positive or negative) on society through their actions and decisions. Given this reality, it is important that they are held responsible and accountable for the consequences of their actions. This concept is often referred to as ‘social responsibility’. However, ‘social responsibility’, as currently conceived in the literature, neglects a specific focus on health as a social goal. Additionally, there are no practical tools to capture this concept in a holistic way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…These studied corporate activity that impacts health across the UCIs of tobacco, 45 - 47 alcohol 18 and ultra-processed food 35 , 37 and the monitoring of the impact of corporate practices on health across industries. 9 , 17 , 36 , 41 , 42 , 48 , 49 Two studies, Trochim et al and Stillman et al, were regionally specific to North America and Asia, respectively. Where multiple studies existed that included the identified framework, the original article was included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studied corporate activity that impacts health across the UCIs of tobacco, 45 - 47 alcohol 18 and ultra-processed food 35 , 37 and the monitoring of the impact of corporate practices on health across industries. 9 , 17 , 36 , 41 , 42 , 48 , 49 Two studies, Trochim et al and Stillman et al, were regionally specific to North America and Asia, respectively. Where multiple studies existed that included the identified framework, the original article was included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Such an endeavour is likely to require cross-disciplinary work, prioritisation of practices and innovation due to the reach of corporate practices into areas outside of national departments of health’s traditional remit. 35 , 49 However, given the number, reach and power of corporations, there has never been a more critical time to develop effective mechanisms to improve accountability of these private sector entities for their public health impacts. 127 , 128 …”
Section: Discussionmentioning
confidence: 99%
“…[1] Pengimplementasian CSR yang salah satu nya memperhatikan kesehatan dapat mempengaruhi kinerja karyawan karena ideal nya menurut OSRAH (Organitation Social Responsibility and Accountability for Health) yang mendapatkan pengimplementasian CSR adalah karyawan dan keluarganya, klien dan kontraktor, komunitas lokal, masyarakat dan lingkungan. Selain meningkatkan kinerja karyawan dapat pula dukungan dari masyarakat dan lingkungan untuk meningkatkan perusahaan tersebut [34] Pengimplementasian CSR yang secara bertahap dan terus menerus akan terus mempertahankan invesor yang berinvestasi dan tidak menutup kemungkinan investor semakin banyak yang tertarik sehingga dana yang dibuttuhkan perusahaan akan cukup untuk kepentingan pembangan perusahaan tersebut. [35] Pengimplementasian dari CSR diharapkan dapat terciptanya inovasi dari program sosial,lingkungan , dorangan mental, atau keberanian dalam menciptkan kinerja baru, ruang baru, layanan proses dan produk baru yang di ciptakan oleh karywan itu sendiri tanpa adanya keterpaksaan dari pihak pemegang [2] sifat yang dinamis dan responsif pemangku kepentingan, menggambarkanCSR sebagai proses perubahan organisasi yang melibatkan tidak hanya "mengidentifikasidan mengelola harapan pemangku kepentingan "tetapi juga" belajar dari waktu ke waktu dankemampuan untuk memahami konteks spesifik dan diharapkan pertemuan pemangku kepentingan juga mempengaruhi pengimplementasian CSR dari pihak eksternal selain dari pihak internal yaitu manajemen secara sukarela untuk melakukan kegiatan CSR tersebut.…”
Section: Hasil Dan Pembahasanunclassified
“…La salud depende de múltiples factores que están fuera del control de las personas y del sistema sanitario 4 . Esos factores, conocidos como determinantes sociales de la salud (DSS), suponen el 75% del riesgo que las personas tienen de enfermar, dependiendo así su salud de las condiciones de vida que les rodean y no tanto del sistema sanitario 5 .…”
Section: Sr Editorunclassified